Model-Based Dose Identification of Dalbavancin for Long-Term Suppressive Outpatient Treatment of Ventricular Assist Device Infections - Ute Chiriac; Uwe Liebchen; Otto Roman Frey; Heike Lanzinger; Sabrina Klein; Torsten Hoppe-Tichy; Matthias Karck; Anna Meyer; Benedict Morath (MDPI AG, 2024)
Increasing evidence suggests that dalbavancin is an effective long-term treatment for ventricular assist device (VAD) infections, with various prolonged dosing regimens currently in use. This retrospective study aimed to assess dalbavancin pharmacokinetics in VAD patients and identify optimal, feasible dosing regimens for long-term suppressive outpatient therapy. Data from Heidelberg University Hospital's VAD register were analyzed using non-linear mixed-effects modeling for pharmacokinetic analysis and dosing simulations (Lixoft®). The probability of target attainment (PTA) and cumulative fraction of response (CFR) were calculated for different protein-binding scenarios considering the minimum inhibitory concentration (MIC) distribution of Staphylococcus aureus. Using data from 13 patients with 38 blood samples, a two-compartment model best described the dalbavancin pharmacokinetics, with a typical value for clearance of 0.050 L/h, central volume of distribution of 6.5 L, and peripheral volume of 15.4 L. No covariates significantly improved the model fit. The observed protein binding varied between 96 and 98%. Dosing simulations demonstrated that 1500 mg every 3 weeks ensured the target attainment for stasis at MIC values of 0.125 mg/L (PTA ≥ 90%) up to a protein binding of 99%. Considering the CRF, longer dosing intervals up to 5 weeks might be possible. Depending on individual MICs and protein binding, a dalbavancin regimen of 1500 mg every 3 to 5 weeks therefore appears to be a valuable option for outpatient therapy of VAD infections. Therapeutic drug monitoring should be considered to manage inter-individual variability and to support clinicians in long-term treatments of subacute and chronic infections.